N-type H2-doped amorphous silicon layer for solar-cell application - Soni Prayogi; A. Ayunis; Yoyok Cahyono; D. Darminto (Materials for Renewable and Sustainable Energy, 2023)
Abstract In this work, we report that hydrogen (H2) doped in n-type a-Si:H thin films strongly influences the electronic correlation in increasing the conversion output power of solar cells. Type n a-Si:H thin films were grown using PECVD on ITO substrates with various H2-doping, to obtain various thin films for solar-cell applications. N-type a-Si:H thin films were prepared, and then characterized using ellipsometric spectroscopy, atomic force microscopy, Fourier transform infrared spectroscopy, and transmission electron microscopy. The addition of doped-H2 to the thin layer shows a decrease in optical conductivity, while the energy gap in the thin layer shows a significant increase in the a-Si:H-type thin layer. Our results show that H2 doping plays a very important role in the electronic structure, which is indicated by the significant energy gap difference. On the other hand, the bond structure of each H2-doped thin film showed a change from amorphous to nanocrystalline structures which were evenly distributed in each H2-doped bonding. Overall, we believe that the addition of doped-H2 to our findings could help increase the power conversion output of the solar cell due to the modification of the electronic structure.